1964
DOI: 10.1161/01.cir.29.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Myocardial Blood Perfusion in Man with Radioactive Potassium or Rubidium and Precordial Counting

Abstract: The myocardial clearance of potassium may be obtained by precordial counting after a single intravenous injection of K 42 Cl or Rb 86 Cl. The theoretical foundations of the method and the technic developed have been presented and discussed. The distribution of the values obtained in normal subjects and in subjects with coronary insufficiency is in agreement with the clinical expectancy, and changes of the observed MCK after nitroglycerin agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1966
1966
1998
1998

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…[16][17][18][19][20] In cases where there is some delay in measuring the potassium activity, there may be uneven losses from the myocardium and the distribution of potassium activity may not represent true distribution of myocardial blood flow. However, the loss of potassium from dog hearts has been shown to be considerably delayed, with approximately 80% of plateau levels remaining at 120 min.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] In cases where there is some delay in measuring the potassium activity, there may be uneven losses from the myocardium and the distribution of potassium activity may not represent true distribution of myocardial blood flow. However, the loss of potassium from dog hearts has been shown to be considerably delayed, with approximately 80% of plateau levels remaining at 120 min.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups of investigators have used radiolabeled Rb' and K+ and precordial detectors to make estimates of "total myocardial flow" in milliliters per minute in the hearts of control subjects and patients with coronary atherosclerosis. Wlhile the data is coInflicting, the majority of workers have reported reductions of total myocardial flow in coronary artery disease (37)(38)(39)(40). This suggests that the reduced myocardial flow/unit mass in twro-and three-vessel disease resulted predominantly from a diminution in coronary blood flow rather than from an increase in the mass of tissue.…”
Section: Regional Myocardial Perfusion and Coronary Arteriographic Lementioning
confidence: 97%
“…In addition, Donato et al (16) confirmed that CBF in man could be accurately determined on the basis of the fractional distribution of these two tracers. These findings suggest that thallium-201, which is biologically similar to potassium, can be utilized to measure CBF.…”
mentioning
confidence: 93%